Ethnicity, Trauma, and Ethical Responsibility: The Mizrahi Woman in the New Israeli Cinema - Yosef, Raz (MiKAN, 2013)
The article explores the relationship between trauma, gender, and ethnicity in the Israeli film Or (Keren Yedaya, 2004). The film presents several routine days in the life of Ruti, a Mizrahi prostitute, and her daughter, Or. I argue that Or is a critical Mizrahi feminist film, one that exposes the hegemonic social gaze as a political mechanism of power and violence terrorizing the Mizrahi female body. The ethnic, class and gender oppression of the Mizrahi female subject—an oppression she comes to internalize—creates a traumatic experience which is expressed both in the film’s narrative and in its cinematic apparatus. Because the trauma is chronic, it cannot be transformed into post-traumatic memory, and so the Mizrahi woman is destined to repeat it over and over again. Two of the film’s aesthetic strategies—the immobile camera and the absence of reverseshots— expose the realistic illusion of cinema and disrupt the viewers’ (especially the male viewers’) identification with the cinematic image. This “wounding” of the cinematic apparatus traumatizes the viewers, demanding that they take ethical responsibility for the traumatization of the Mizrahi female body in Israeli society.